Development of Physical Activity Competence Test Battery and Evaluation Standards for Korean Children - Yeon-Oh Han; Byung-Sun Lee (MDPI AG, 2022)
The purpose of this study is to develop a comprehensive and systematic method and standard for evaluating children's physical activity competency as a solution to the problem of increasing child obesity rates due to a decrease in physical activity among children. This study was used a cross-sectional study design. A literature review and Delphi survey were conducted to develop children's physical activity competency evaluation. The evaluation criteria were presented based on the measurement data of metropolitan area kindergarten students (228 subjects) on the 2016 winter vacation. Items in the evaluation of children's physical activity competency test battery include health physical strength, basic movement skills, physical activity habits, and physical activity attitudes. Physical fitness for health consisted of muscle strength and endurance (sit-up), flexibility (sit and reach, trunk lift) and body composition (BMI). Fundamental movement skills consisted of mobility (run, hop, jump), stability (static balance, dynamic balance), and control (throw kick). Physical activity habits consisted of the amount of daily steps (steps), exercise time, screen time, and sleep time. Physical activity attitudes consisted of preference, enjoyment, and confidence. The evaluation criteria for child physical activity competency test battery were presented in five stages, divided by age and gender. With the developed evaluation of children's physical activity competency, the overall level of physical fitness for health, fundamental movement skills, physical activity habits, and physical activity attitudes of kindergarteners in the metropolitan area could be confirmed, and standards were presented.